Resilience Communication of Micro-Enterprise Actors in the Service Sector Affected by COVID-19 in Depok, West Java - Ekayanthi, Daesy; Lubis, Djuara P.; Sumardjo, Sumardjo; Sarwoprasodjo, Sarwititi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Micro businesses are essential to national economic development by generating jobs, increasing income, and reducing poverty. The Covid-19 pandemic had a severe impact, especially on micro businesses in the service sector, with restrictions causing reduced consumer demand and business closures, including in Depok, West Java. Effective communication was critical for their resilience, enabling quick response, accurate information, marketing adaptation, customer engagement, network strengthening, collaboration, and innovation. This research aims to analyze the communication practices of micro business actors in the service sector affected by the Covid-19 pandemic in Depok, West Java. Using a qualitative approach with an interpretive paradigm, the study employed interviews and observations, applying communication theories from Betts and Buzzanell in an economic context. Findings reveal the importance of effective communication processes for micro business resilience during crises. Key sources of information and discussion for these businesses during the pandemic included micro business communities, family and friends or colleagues, and social media.